Supplementation of Microbial Phytase with Safflower Meal in Rainbow Trout (Oncorhynchus mykiss): The Effects on Growth, Digestibility, Environmental, and Serum Biological Parameters - İsmail Berat Çantaş; Önder Yildirim (Journal of Chemistry)
This study aimed to determine the effects of diets replacing soybean meal with safflower meal and phytase enzyme on feed utilization, growth performance, body composition, serum biological parameters, and environmental effects of rainbow trout (Oncorhynchus mykiss). To this aim, five different isonitrogenous (44%) and isocaloric (23 kJ) experimental feeds were formulated as follows: the control group (C) containing no safflower meal and enzyme; SFM10 and SFM20 groups containing 10% and 20% of safflower meal instead of soybean meal, respectively; and SFM10 ± P1000 and SFM20 ± P2000 groups containing 10% safflower meal and 1000 IU/kg phytase and 20% safflower meal and 2000 IU/kg phytase, respectively. Juveniles (12.57 ± 3.05 g average weight) were fed for 60 days. As a result, the best growth rate and feed conversion were recorded in the SFM20 ± P2000 group with 127.07 ± 7.73% and 1.13 ± 0.020, respectively p<0.05. On the contrary, total phosphorus in SFM20 ± P2000 group trial feed was 1.20 ± 0.02, while 0.70 ± 0.08 was found in feces that is the best result between other groups. ALP, LDH, TPROT, CHOL, and triglyceride levels were not statistically different among the experimental groups. ALT, AST, glucose, and albumin levels in serum resulted to be affected by different phytase levels but without any negative effect on fish growth and fish health status. Cholesterol level in the SFM10 ± P1000 group was the highest and positively affected growth and health status of this group. In conclusion, 20% safflower meal replacement along with 2000 IU/kg microbial phytase in feeds can be considered suitable for rainbow trout due to its sustainability and reduced environmental effects due to reduced phosphorous excretion.